KEBIJAKAN PEMERINTAH DALAM PENANGANAN PANDEMI COVID-19 - Darmin Tuwu (Universitas Halu Oleo, 2020)
This paper aims to elaborate on how government policies prevent and deal with COVID-19. The method used is a qualitative method with a case study approach. The focus of the study is government policies and events that follow the implementation of the policy period from March to June 2020 related to government policies in the prevention and treatment of COVID-19. The study results show that government policies to prevent the spread of Coronavirus transmission such as the policy of staying at home; Social distancing; Physical Restrictions; Use of Personal Protective Equipment; Maintain Personal Hygiene; Work and Study at home; Postpone all activities that gather a lot of people; Large-scale social restrictions; until the implementation of the New Normal policy. In addition, the government has also implemented social assistance and social protection policies to ensure that the community can survive, not only the Social Welfare Services Government group but also the high-class community.